Cormac McCarthy’s Aesthet(h)ics of the “Canal-Rhizome” in Suttree - Marie-Agnès Gay (European Journal of American Studies)
This essay interprets Suttree’s (1979) obsessional themes of vagrancy and in-betweenness, and their aesthetic inscription in the text by resorting to Gilles Deleuze and Felix Guattari’s motif of the “canal-rhizome” as developed in Mille plateaux (1980). Close textual analysis reveals that, in parallel to his hero’s embracing of social liminality in rebellion to his father’s conservative value system based on law and order, McCarthy makes the ethical choice of “pass-words” over “order-words,” of transforming “compositions of order” into “components of passage,” a militant act of literary commitment. Moreover, the essay contends that the text’s aesthetic choice of liminal forms is also meant to enable the reader to share the hero’s metaphysical experience of the mysteries of death-in-life.